Tempestuous Course of Enterococcus Infective Endocarditis — From Daptomycin Lung Toxicity to Successful Treatment With Surgery and Fosfomycin Combination Therapy. Issue 2 (March 2020) - Gupta, Neha; Sah, Ranjit; Chawla, Sony; Kasliwal, Ravi R.; Tarique, Ahmar; Mehta, Yatin; Trehan, Naresh
Abstract : Abstract: Management of enterococcal infective endocarditis (IE) is one of the intriguing challenges in infectious diseases. Ampicillin with gentamicin is the standard therapy for susceptible Enterococcus faecalis . However, in presence of β-lactam-resistant isolates, nephroxicity, or allergy to β-lactams, alternatives like glycopeptides and daptomycin have been used for the treatment of enterococcus IE. We report a patient with E. faecalis IE who had allergy to β-lactam and during treatment had developed daptomycin lung toxicity. He was subsequently treated with intravenous fosfomycin and surgery with aortic valve replacement. Abstract : Management of enterococcal infective endocarditis (IE) is one of the challenging infectious diseases syndromes. The authors report a patient with Enterococcus faecalis IE with allergy to β-lactam who had developed daptomycin lung toxicity during therapy. He was subsequently treated with intravenous fosfomycin and surgery. This case highlights the need for clinicians to recognize and appropriately manage daptomycin-induced lung toxicity.